2004
DOI: 10.1084/jem.20041006
|View full text |Cite
|
Sign up to set email alerts
|

CD8 Epitope Escape and Reversion in Acute HCV Infection

Abstract: In the setting of acute hepatitis C virus (HCV) infection, robust HCV-specific CD8+ cytotoxic T lymphocyte (CTL) responses are associated with initial control of viremia. Despite these responses, 70–80% of individuals develop persistent infection. Although viral escape from CD8 responses has been illustrated in the chimpanzee model of HCV infection, the effect of CD8 selection pressure on viral evolution and containment in acute HCV infection in humans remains unclear. Here, we examined viral evolution in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
320
2
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(338 citation statements)
references
References 54 publications
11
320
2
5
Order By: Relevance
“…HCV genotype was probably not a factor in the outcome of PD-1 blockade. The quality of T-cell immunity varies widely in humans and chimpanzees even when infection is established with viruses of the same genotype or subtype (7,13,14,(24)(25)(26)(27)(28)(29). It is therefore likely that successful PD-1 therapy in Ch5300 was due to priming and/or maintenance of a broad T-cell response that could be rescued regardless of HCV genotype.…”
Section: Resultsmentioning
confidence: 99%
“…HCV genotype was probably not a factor in the outcome of PD-1 blockade. The quality of T-cell immunity varies widely in humans and chimpanzees even when infection is established with viruses of the same genotype or subtype (7,13,14,(24)(25)(26)(27)(28)(29). It is therefore likely that successful PD-1 therapy in Ch5300 was due to priming and/or maintenance of a broad T-cell response that could be rescued regardless of HCV genotype.…”
Section: Resultsmentioning
confidence: 99%
“…22 For example, Timm et al 73 recently observed a strong association between sequence variation within an immunodominant HLA-B*8 restricted NS3 epitope and expression of HLA-B*8, also supporting reproducible allele-specific selection pressures at the population level. Ray et al 74 performed a study in the well-documented Irish cohort and compared sequences present in serum obtained 18-22 years after infection to sequences present in the shared inoculum.…”
Section: Role Of Class I Alleles In Hcv Infectionmentioning
confidence: 94%
“…Carriage of the restricting HLA allele was associated with viral polymorphisms at several sites within immunogenic epitopes, consistent with viral escape from HLA-restricted immune pressure. At multiple sites, including experimentally established viral escape sites (for example, NS3-1397-1398 for HLA-B*0801 and NS5B-2841 and 2846 for HLA-B*2705 20,[23][24][25], there was nearly complete conservation in the alternative genotype, even in individuals carrying the relevant HLA alleles (Fig. 2).…”
Section: Amino Acid Variation Within Published and Predicted Viral Epmentioning
confidence: 99%